A review on hydrothermal co-liquefaction of biomass. (15th September 2019) - Yang, Jie; (Sophia) He, Quan; Yang, Linxi
Highlights: Co-liquefaction of a variety of biomass feedstocks. Model development for product yield prediction in co-liquefaction. Interactions among biomass model components under co-liqufaction conditions. Abstract: Hydrothermal co-liquefaction of biomass has attracted considerable research interest as it has potential to reduce logistics costs, increase biocrude yield and improve biocrude quality. This work summarizes hydrothermal co-liquefaction of various biomass, in which co-liquefaction effect (either synergistic, antagonistic or additive) on biocrude yield of was examined. Observed synergetic effects must be critically assessed due to inconsistent reaction/separation conditions, uncertain statistical significance of experimental data and varied indicator of co-liquefaction effect in the studies reported. The chemical interactions among biomass model components (cellulose, hemicellulose, lignin, lipid, and protein) were also thoroughly investigated to explore the origin of co-liquefaction effect. Recent progresses on modeling hydrothermal liquefaction was reviewed as well, including quantitative models for predicting product yield as a function of the biochemical composition of biomass feedstock and/or reaction parameters, and kinetics models of reaction network among individual component of biomass. These models are useful tools to investigate co-liquefaction effect, optimize feedstock mixing for co-liquefaction, and ultimately facilitate more efficient biomass conversion. The major challenges in the study of co-liquefaction are identified such as statistical significance of co-liquefaction effect, evaluation of co-liquefaction effect under identical liquefaction and separation conditions, and understanding of co-liquefaction effect at a molecular level.